Alexithymia in patients with Parkinson’s disease treated with DBS of the subthalamic nucleus: a case-control study. - Lorys eCastelli; Debora eTonello; Laura eRizzi; Maurizio eZibetti; Michele eLanotte; Leonardo eLopiano (Frontiers in Psychology, 2014)
ObjectivesTo evaluate the effect of deep brain stimulation of the subthalamic nucleus (STN-DBS) on alexithymia, a deficit in affective regulation, comparing patients with Parkinson’s disease (PD) submitted to STN-DBS (DBS group) to PD patients not yet treated with STN-DBS (pre-DBS group) and to healthy participants (C group). MethodsWe recruited 27 consecutive STN-DBS PD patients, 38 consecutive pre-DBS patients and 27 healthy participants. Patients were assessed for alexithymia (Toronto Alexithymia Scale), depression (Beck Depression Inventory) and cognitive functions (reasoning, memory, attentional and executive tests). ResultsThe DBS patients performed worse than the pre-DBS patients in the Corsi’s Block-Tapping Test, in the phonemic fluency task and in the Frontal Assessment Battery. 29.6% DBS and 31.6% pre-DBS patients resulted alexithymic, compared with14.8% in the C group. Results pointed out significantly higher alexithymia scores in both the DBS and pre-DBS groups compared with the C group, while no difference emerged between the DBS and pre-DBS groups. Pre-DBS group showed a significantly higher BDI score than the C group, while DBS group did not. ConclusionAlthough the results suggest that STN-DBS does not affect alexithymia, both the DBS and pre-DBS patients reported higher prevalence (about 30%) of alexithymia than did healthy subjects (14.8%).